Hubungan Pengetahuan, Sikap dan Perilaku Masyarakat dengan Kesediaan dalam Mengikuti Vaksinasi COVID-19 - Shania Fanty Anggrek; Elpira Asmin; Alessandra F. Saija (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2023)
Coronavirus disease 2019 or commonly called COVID-19 is an infectious disease that is now a global pandemic. COVID-19 is now a serious problem all over the world, the number of cases is also increasing every day. Therefore, it is not only necessary to intervene in the implementation of health procedures but also to immediately take other effective intervention measures to stop the spread of disease, namely through vaccination efforts. This study aims to determine the relationship between knowledge, attitudes and community behavior towards COVID-19 vaccination with willingness to participate in COVID-19 vaccination in Passo Village in 2022. This research is a quantitative analytic study using a cross sectional research design. Samples were taken as many as 100 people using a combination of purposive sampling and stratified sampling methods. The results showed that knowledge about the COVID-19 vaccine was 44% (currently), community attitudes towards the COVID-19 vaccination program were 71% (good), community behavior towards COVID-19 prevention was 75% (good) and willingness to participate in the COVID-19 vaccination was 75 % (willing to be vaccinated against COVID-19). The results of the bivariate analysis using the chi-square stated that there was a significant relationship between knowledge (p=0.024), attitude (p=0.027) and behavior (p=0.006) with willingness to participate in COVID-19 vaccination in the village in 2022.